2012
DOI: 10.1371/journal.pone.0030696
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity and Fatty Liver Are Reduced by Plant-Derived Pediococcus pentosaceus LP28 in High Fat Diet-Induced Obese Mice

Abstract: We evaluated the effect of an oral administration of a plant-derived lactic acid bacterium, Pediococcus pentosaceus LP28 (LP28), on metabolic syndrome by using high fat diet-induced obese mice. The obese mice were divided into 2 groups and fed either a high fat or regular diet for 8 weeks. Each group was further divided into 3 groups, which took LP28, another plant-derived Lactobacillus plantarum SN13T (SN13T) or no lactic acid bacteria (LAB). The lean control mice were fed a regular diet without inducing obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 28 publications
4
76
0
Order By: Relevance
“…Despite L. plantarum decreasing the plasma glucose level in a highfat diet fed mice, the energy intake, body fat content and plasma cholesterol were not different compared to the control group. In other studies, Enterococcus, Lactobacillus and Bifidobacterium were also not observed lower plasma cholesterol in C57BL/6J mice fed a high-fat diet [2,20] In this study, there was no significant difference in the energy intake and plasma T-cho concentration between the HD and HLD groups (Table 2). Therefore, it was supposed that Lb.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Despite L. plantarum decreasing the plasma glucose level in a highfat diet fed mice, the energy intake, body fat content and plasma cholesterol were not different compared to the control group. In other studies, Enterococcus, Lactobacillus and Bifidobacterium were also not observed lower plasma cholesterol in C57BL/6J mice fed a high-fat diet [2,20] In this study, there was no significant difference in the energy intake and plasma T-cho concentration between the HD and HLD groups (Table 2). Therefore, it was supposed that Lb.…”
Section: Discussionsupporting
confidence: 45%
“…The cholesterol-reducing effect by LAB is known to occur through high cholesterol adsorption on the cell body, and increased bile acid adsorption ability [28,29]. Hepatic cholesterol contents have been shown to be significantly lowered by LABs such as Lactobacillus gasseri and Pediococcus pentosaceus [2,30] In another study on rodents fed a high-fat diet, the hepatic cholesterol content was significantly lowered by P. pentosaceus, and lipid metabolismrelated genes such as cluster of differentiation 36 (CD36) and stearolCoA desaturase 1 (SCD1) showed decreased expression [2] It is necessary to investigate the effect of this strain on mRNA expression in the liver in mice fed HD. We predict that Lb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that some strains stocked in the LAB library are useful for enhancing intestinal immunity, improving liver function, and preventing metabolic syndrome. [3][4][5][6] LAB fermentation often proceeds even at low temperatures, causing the overgrowth of LABs. As the result, the degradation of flavors is proceeded and affected with taste of the fermented foods.…”
mentioning
confidence: 99%